A Case Study Of Digi's Branding Success - Phang, Sin Mun (2008)
This study tracks the course DiGi took to bring about a recognizable brand name from its humble origin. The study look at the alignment of branding with DiGi vision and mission as well as other corporate efforts to deliver its promise to customers and stakeholders alike against competition.